(untitled) - Nettels, Curtis P. (London, 1962)
Part of a series of detailed reference manuals on American economic history, this volume traces the development of agriculture, transportation, labour movements and the factory system, foreign and domestic commerce, technology and the ramifications of slavery.
Keywords: United States; Economic conditions